2016
DOI: 10.21767/2471-8505.100025
|View full text |Cite
|
Sign up to set email alerts
|

A Retrospective Review of High versus Standard Dose Dexmedetomidine for Sedation in Critically Ill Patients

Abstract: Introduction: Studies have demonstrated safety and efficacy of dexmedetomidine infusions at doses up to 1.5 mcg/kg/hr. Data evaluating doses greater than 1.5 mcg/kg/hr is limited; however, up to 2.5 mcg/kg/hr has been utilized. It is uncertain whether higher doses provide additional benefit but may result in more adverse events. The purpose of this study was to compare the safety and efficacy of dexmedetomidine at high doses (greater than 1.5 mcg/kg/hr) versus standard doses (0.2 to 1.5 mcg/kg/hr). Methods:A r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(13 citation statements)
references
References 13 publications
3
9
0
1
Order By: Relevance
“…A study by Rodriguez et al analyzed 120 patients who received dexmedetomidine for at least 24 hours. 8 They found that patients who received a maximum dexmedetomidine dose ≤1.5 mcg/kg/hour (n = 51), spent more time within the goal RASS range of −2 to +1 than patients who had a high dose As expected, we also found that patients who received higher doses of dexmedetomidine were more likely to require an additional sedative agent. This is in agreement with both Jones et al and Rodriguez et al who both reported higher use of additional sedative agents in the high dose group (53.5% vs 26.8%; P = .003 and 87% vs 67%; P = .008, respectively).…”
Section: Discussionsupporting
confidence: 71%
See 4 more Smart Citations
“…A study by Rodriguez et al analyzed 120 patients who received dexmedetomidine for at least 24 hours. 8 They found that patients who received a maximum dexmedetomidine dose ≤1.5 mcg/kg/hour (n = 51), spent more time within the goal RASS range of −2 to +1 than patients who had a high dose As expected, we also found that patients who received higher doses of dexmedetomidine were more likely to require an additional sedative agent. This is in agreement with both Jones et al and Rodriguez et al who both reported higher use of additional sedative agents in the high dose group (53.5% vs 26.8%; P = .003 and 87% vs 67%; P = .008, respectively).…”
Section: Discussionsupporting
confidence: 71%
“…This is in agreement with both Jones et al and Rodriguez et al who both reported higher use of additional sedative agents in the high dose group (53.5% vs 26.8%; P = .003 and 87% vs 67%; P = .008, respectively). 8,9 These findings show that adjunct sedation is often needed despite increased doses of dexmedetomidine. This may in part be explained by the pharmacodynamic properties of dexmedetomidine, which has historically not been considered to be deeply sedating, and thus requirement for additional sedation may be expected despite use of higher doses.…”
Section: Discussionmentioning
confidence: 86%
See 3 more Smart Citations